Perbandingan Perhitungan Kalkulasi Biaya Menggunakan Metode Traditional Costing dan Activity Based Costing - Rina Sandora; Abdul Halik; Siti Mujanah (Universitas Pendidikan Ganesha, 2026)
The current high level of market competition is often not accompanied by changes in cost accounting systems for calculating product costs. The use of traditional cost accounting systems is starting to be abandoned, especially in allocating overhead costs to products. This study aims to accurately determine cost calculations by comparing the results of cost calculations using traditional cost accounting systems with the Activity-Based Costing (ABC) system. The results of this study indicate that cost calculations with the Activity Based Costing (ABC) system are more accurate than the traditional cost accounting system. The cost calculation using the traditional system obtained a cost per unit for product type A of Rp. 39.238 and product type B of Rp. 29.013. The results of Activity Based Costing (ABC) obtained a cost per unit for product type A of Rp. 37.034 and product type B of Rp. 31.417.